THE ENVIRONMENT OF WORK BALANCED AS A FUNDAMENTAL RIGHT (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article will seek to present the balanced work environment as a fundamental right, since the search for thewell-being and safety of workers are  constitutional guarantees. It is noted that the corporate world is increasingly aware of the relevance of quality of life and the need to develop and apply better conditions for the well-being of workers. Thus, this search for quality of life is part of the context of social responsibility, a practice that must be aggregated both by companies and by professionals themselves. Moreover, in a highly competitive environment where companies are inserted, it causes countless managers not to direct their attention to the work environment, providing their employees and, consequently, not to verify the damage to which they are exposing their employees in their workplace, to the environment and to the communities. . The methodology used in the present study is based on the literature review.